Integrated TWAS, GWAS, and RNAseq results identify candidate genes associated with reproductive traits in cows - Sevda Hosseinzadeh; Seyed Abbas Rafat; Lingzhao Fang (Scientific Reports)
Abstract Low fertility in cows leads to early removal from herds. Since reproductive traits are complex and have low heritability, genetic analysis can aid in improving reproduction. This study identified key genes linked to fertility by conducting genome- and transcriptome-wide association studies, RNA-seq analysis, meta-analysis, weighted gene co-expression network analysis, and functional enrichment analysis. Through these methods, we identified candidate genes related to Cow conception rate (CCR), Daughter pregnancy rate (DPR), Heifer conception rate (HCR), and overall fertility traits, helping to improve genetic selection for reproductive success in cows. The identified genes include RPL12, FKBP1B, FZD10, COX10, COX7A2, GAA, ETFBKMT, ACSM5, NUDT9, TIGAR, PAIP2, and PSMB5. Notably, GAA, ETFBKMT, COX10, and COX7A2 are involved in the “generation of precursor metabolites and energy” process. COX10, GAA, ETFBKMT, ACSM5, NUDT9, and TIGAR exhibit significant impacts on CCR, DPR, and HCR. COX7A2, PAIP2, and PSMB5 have been identified as hub genes related to fertility traits. RPL12 plays a role in protein synthesis, essential for gametogenesis and embryo development, while FKBP1B regulates calcium signaling, particularly in oocyte aging and fertility decline, and FZD10 is crucial in Wnt signaling. The identified genes serve as markers for genomic selection aimed at enhancing reproductive traits in cow.